An assessment of Bangabandhu Sheikh Mujib Medical University for improving the research capacity. (2021) - Rayna, Shahrin Emdad; Khalequzzaman, Md; Khan, Fahmida Afroz; Rahman, K M Thouhidur; Mehnaz, Novera; Jahan, Nusrat; Hakim, Ferdous; Zaman, M Mostafa; Islam, Syed Shariful
No abstract available